PERSEPSI REMAJA TERHADAP SEXTING DI MEDIA SOSIAL - Rafles Abdi Kusuma (Prodi Jurnalistik Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
This article aims to discuss about sexting, which is a social phenomenon that is currently happening, especially among teenagers. Sexting activity is a method of interaction through social networks in adolescents that is being reconstructed and redefined through communication technology. The vulnerability of teenagers to sexting on social media cannot be denied. A sexting case recently occurred in Bangka 2019, namely a threat to young women from Pangkalpinang who were forced to do topless chests while making video calls on whatsapp social media. Based on a review of previous studies examining the phenomenon of sexting, the findings of these studies have shown a tendency for teenagers in the world to consider sexting a